2007
DOI: 10.1038/modpathol.3800765
|View full text |Cite
|
Sign up to set email alerts
|

Micropapillary pattern and grade of stromal invasion in pT1 adenocarcinoma of the lung: usefulness as prognostic factors

Abstract: Recently, the stromal invasion grading system was proposed for small adenocarcinomas of r2.0 cm. The system is based on the presence or absence of a fibrotic focus, and the extent of invasion into the fibrotic focus. Although stromal invasion grading system closely correlated with the prognosis, stromal invasion grade 3, representing stromal invasion into the center of a fibrotic focus, was the largest group of tumors and showed variable prognosis. In this study, we investigated whether stromal invasion gradin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 32 publications
(41 reference statements)
5
50
0
Order By: Relevance
“…28,29 The adverse prognosis associated with the micropapillary pattern, confirms observations in multiple previous studies and supports the addition of this new subtype to the classification. 10,11,[30][31][32][33] However, varied criteria for the diagnosis have been used with percentage of the micropapillary component including as little as 6% of the total tumor and none of these studies have utilized comprehensive histological subtyping to define this subgroup according to the predominant subtype showing comparison with survival of the other histological subtypes as we have done. 10,11,[30][31][32][33] Our finding that colloid adenocarcinomas also fit into this poor prognostic group was somewhat surprising as these tumors are often regarded as well-differentiated tumors, but this is the largest series of these tumors reported where survival analysis compared outcome with other adenocarcinoma histological types.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The adverse prognosis associated with the micropapillary pattern, confirms observations in multiple previous studies and supports the addition of this new subtype to the classification. 10,11,[30][31][32][33] However, varied criteria for the diagnosis have been used with percentage of the micropapillary component including as little as 6% of the total tumor and none of these studies have utilized comprehensive histological subtyping to define this subgroup according to the predominant subtype showing comparison with survival of the other histological subtypes as we have done. 10,11,[30][31][32][33] Our finding that colloid adenocarcinomas also fit into this poor prognostic group was somewhat surprising as these tumors are often regarded as well-differentiated tumors, but this is the largest series of these tumors reported where survival analysis compared outcome with other adenocarcinoma histological types.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of these other patterns includes poorer prognosis in micropapillary [22][23][24][25][26][27] cancer with a higher rate of node metastasis, and emerging observations of poorer prognosis in solid type adenocarcinoma. 17,28 In addition, certain histological subtypes have been associated with specific molecular alterations, such as KRAS mutation in mucinous adenocarcinoma, 29 EML4-ALK translocation in cribriform mucinous and signet ring type adenocarcinoma, 30,31 and b-catenin mutations in fetal type adenocarcinoma.…”
Section: Invasive Adenocarcinoma Patternsmentioning
confidence: 99%
“…Patient prognosis for IMPV has not been clarified extensively. However, it is well known that lymph node metastasis is one of the most important prognostic factors in gallbladder cancer (5,23,30), and several prior studies of the other organs have shown a strong association between IMPV histology and shortened patient survival (11,20,21). We speculate that the patient prognosis of carcinomas with IMPV is poorer than a conventional carcinoma of the gallbladder.…”
Section: Discussionmentioning
confidence: 46%